Learnviro: An IoT-Based Innovation for Monitoring the Learning Environment - Maryani, Ika; Okimustava, Okimustava; Suyatno, Suyatno; Hasanah, Enung (Universitas Ahmad Dahlan, 2025)
Background: Aisyiyah Bantul's Leading Elementary School faces challenges in maintaining an optimal learning environment, particularly regarding temperature, humidity, and lighting. This community service program introduces Learnviro, an IoT-based solution for real-time environmental monitoring, enabling schools to make data-driven decisions to enhance learning conditions. Contribution: Learnviro empowers teachers by providing real-time data, allowing them to make informed adjustments that support differentiated instruction. The system also improves school management by optimizing classroom conditions and infrastructure maintenance. Method: The program consists of four stages: (1) collaboration with partner schools to assess needs, (2) installation of IoT devices in classrooms, (3) teacher training on interpreting and applying environmental data, and (4) continuous technical support. Data collection involved observations, interviews, and questionnaires, analyzed descriptively to evaluate the program’s effectiveness. Results: Learnviro effectively provided real-time environmental data, improving teachers’ proficiency in utilizing IoT-based insights for classroom management. Students reported increased comfort and focus, while schools experienced better infrastructure maintenance through data-driven decision-making. Conclusion: Learnviro has proven to be an effective tool for optimizing classroom conditions and empowering the school community. By integrating IoT technology into education, this initiative demonstrates the practical application of intelligent environmental monitoring in addressing real-world.